Is the Transition to Renewable Energy Consumption Hampered by High Oil Prices? - Mukhtarov, Shahriyar; Humbatova, Sugra; Hajiyev, Natig Gadim-Oglu (International Journal of Energy Economics and Policy, 2021)
The article examines the impact of oil price, income and CO2 emissions on renewable energy consumption in the case of Kazakhstan for the data period from 1992 to 2015, employing FMOLS and CCR methods. Empirical results reached that there is a long-run positive and statistically significant impact of income on the renewable energy consumption whereas a negative effect of oil price and CO2 emissions in Azerbaijan, for the investigated period. The results of this article might be beneficial for the policymakers and support the current literature for next researches for oil-rich developing countries. Keywords: Renewable energy consumption; Income; Oil price; FMOLS; CCR; Kazakhstan JEL Classifications: 013, P28, Q42, Q43 DOI: https://doi.org/10.32479/ijeep.11345